2014
DOI: 10.1111/1750-3841.12669
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Sodium Release Related to Gel Microstructural Properties—Implications for Sodium Reduction

Abstract: The microstructure of food can be engineered to enhance sodium release during mastication, which may be used as a strategy to reduce sodium content in foods. This study aimed to relate sodium release to microstructural properties of solid lipoproteic colloid (SLC) foods. The SLC gels with 1.5% (w/w) NaCl were prepared by homogenization of whey protein isolate and anhydrous milk fat, followed by heat-induced gelation. The gels varied in protein content (8% or 16%), fat content (0%, 11%, 22%, or 33%), and homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 34 publications
(52 reference statements)
5
54
0
Order By: Relevance
“…This tendency is because the fat droplets are structural defects, and defects increase the stress concentration of the gel matrix (Sala, van Vliet, Cohen Stuart, Aken, & van de Velde, 2009;van Vliet, Luyten, & Walstra, 1993). This property has been further demonstrated by reductions in the gel fracture strain, stress or energy and by increases in sodium release with higher fat contents or lower emulsion droplet particle sizes in lipoproteic gels (de Loubens et al, 2011;Kuo & Lee, 2014b;Panouille, Saint-Eve, de Loubens, Deleris, & Souchon, 2011;Phan et al, 2008). Our previous study on model solid lipoproteic colloid (SLC) gels revealed that a higher homogenization pressure led to a lower hydrodynamic radius of the emulsion droplets (r h,e ), which implied an SLC gel network with more randomly dispersed structural defects.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…This tendency is because the fat droplets are structural defects, and defects increase the stress concentration of the gel matrix (Sala, van Vliet, Cohen Stuart, Aken, & van de Velde, 2009;van Vliet, Luyten, & Walstra, 1993). This property has been further demonstrated by reductions in the gel fracture strain, stress or energy and by increases in sodium release with higher fat contents or lower emulsion droplet particle sizes in lipoproteic gels (de Loubens et al, 2011;Kuo & Lee, 2014b;Panouille, Saint-Eve, de Loubens, Deleris, & Souchon, 2011;Phan et al, 2008). Our previous study on model solid lipoproteic colloid (SLC) gels revealed that a higher homogenization pressure led to a lower hydrodynamic radius of the emulsion droplets (r h,e ), which implied an SLC gel network with more randomly dispersed structural defects.…”
Section: Introductionmentioning
confidence: 97%
“…In a model polysaccharide/protein gel, the serum release was found to be higher in a bi-continuous microstructure than in a protein-continuous one (Stieger, 2011). Lastly, the fragmentation degree of lipoproteic foods is greater with higher fat content (de Loubens,et 4 al., 2011), lower protein content (Panouille, et al, 2011), or smaller particle size of the emulsion droplets (Kuo and Lee, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracted parameters from the curves can be used to quantify the sodium release (Kuo & Lee, ). In this study, four parameters were chosen to represent the sodium release profile (Christina & Lee, ): the maximum of sodium release rate ( R max ), the snapshots of sodium concentration at 20 s ( C 50 ), 50 s, and 50 s ( C 150 ).…”
Section: Methodsmentioning
confidence: 99%